1978
DOI: 10.1111/j.1365-3113.1978.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic review of immature dung beetles of the subfamily Scarabaeinae (Coleoptera: Scarabaeidae)

Abstract: Discussion of the taxonomy of scarabaeine larvae includes: (i) a redescription of the subfamily Scarabaeinae based upon larval characters, (ii) descriptions of known genera based upon larvae, and (iii) a key to known genera. Twenty-five genera representing each of the six currently recognized tribes and most subtribes are considered:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 12 publications
1
48
0
4
Order By: Relevance
“…Most recently, Philips et al (2004) produced a comprehensive phylogeny based on 50 genera and 250 characters. Larvae have also been studied for phylogenetic potential (Edmonds & Halffter 1978). They concluded, however, that it was currently impossible to establish coherent suprageneric larval groupings.…”
Section: Phylogeny and Taxonomymentioning
confidence: 97%
See 2 more Smart Citations
“…Most recently, Philips et al (2004) produced a comprehensive phylogeny based on 50 genera and 250 characters. Larvae have also been studied for phylogenetic potential (Edmonds & Halffter 1978). They concluded, however, that it was currently impossible to establish coherent suprageneric larval groupings.…”
Section: Phylogeny and Taxonomymentioning
confidence: 97%
“…anus transverse; (25.) venter of last abdominal segment with one or more distinct rows and/or patches of short setae (raster); raster rarely absent (Edmonds & Halffter 1978).…”
Section: Phylogeny and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the pupal stages of many scarabs have thoracic 'horns', and these are often present in individuals (eg females) or species that lack this horn as adults. Pupal 'horns' may serve a current function as support structures protecting animals during the vulnerable metamorphic molt (Main, 1922;Halffter and Matthews, 1966;Edmonds and Hallfter, 1978), but they may also represent developmental carry-overs from a Figure 6 Partial phylogeny for the families and subfamilies of scarab beetles (Coleoptera: Scarabaeoidea) illustrating lineages with head or pronotal (thorax) horns (approximate no. species in parentheses).…”
Section: Mystery Of the Scarabs Resolved?mentioning
confidence: 99%
“…Studies of larvae suggested that larval mophology could be very useful in the systematic analysis of the Scarabaeoidea (Ritcher, 1966;Edmonds & Halffter, 1978;Verdu et al, 1998) In this study, we describe the third larval instar of Ani soplia (Anisoplia) baetica Erichson, 1847, Anisoplia (Anisoplia) depressa Erichson, 1847, Anisoplia (Anisop lia) remota Reitter, 1889 and Anthoplia floricola (F., 1787). These species are included in a revised key to the larvae of Anisopliini.…”
Section: Introductionmentioning
confidence: 99%